Vibration based diagnosis of wheel defects of metro train sets using one period analysis on the wayside - Kilinc, Onur; Vágner, Jakub (JVE International, 2017)
This research examines two different methods; Wavelet Packet Energy (WPE) and Time-domain Features (TDF) which are effective in faulty signal feature extraction of metro wheels in wayside level using vibration sensors. Signals of each wheelset passing of a trainset with both healthy and faulty wheels are recorded by the vibration sensors which are mounted on both left and right rails and a novel one-period sampling is performed at 51.2 kHz sample rate. Retrieved signal samples are used in the construction of a database which is consistent of healthy and faulty cases. Since the database has insufficient number of faulty samples, the database is balanced by a method so called Adaptive Synthetic Sampling (ADASYN) so that each class has the same number of observations. Two state-of art classifiers; Support Vector Machines (SVM) and Fisher Linear Discriminant Analysis (FLDA) are employed by utilizing 16-fold cross validation to solve the two-class problem. Referring to the results, SVM-I-TDF outperforms by classifying all samples with a success rate of 100 % and other methods have also promising results. Proposed methods may be used in the condition monitoring of metro wheelsets effectively by means of not only performance but also cost-efficiency.
Diagnostika defektů dvojkolí měřením vibrací u trati za použití analýzy jedné otáčky kola
Keywords: wavelet packet energy; time domain features; wheelset fault diagnosis; one period analysis; Fisher linear discriminant analysis; support vector machine; wavelet packet energy; time domain features; diagnostika vad dvojkolí; analýza jedné otáčky; Fisherova lineární diskriminační analýza; support vector machine